THE EFFECT OF CAREER DEVELOPMENT, TRAINING, AND MOTIVATION ON EMPLOYEE PERFORMANCE AT PT. LAMTORO BLANG MANE MEDAN - Desi Rahmawati; Dosri Ompusunggu; Tuty Nainggolan; Richard Berlien (SEAN Institute, 2023)
The purpose of this study is to determine the impact of career development, training and motivation on employee performance at PT. Lamtoro Blang Mane Medan. The population of this study consisted of 187 individuals, while the sample included 57 employees who work in outsourcing. The procedure used in this research is a quantitative approach. This research uses a type of survey by distributing questionnaires to respondents. Data testing was carried out using the classical assumption test and multiple linear regression. The results of this study indicate that partially, career development has no effect on employees at PT. Lamtoro Blang Mane Medan. But in some cases training has a significant impact on employee performance. Besides that, partially, motivation has a significant impact on employee performance. Simultaneously, career development, training, and motivation have a significant effect on employee performance at PT.Lamtoro Blang Mane Medan.